Effect of Fibre Types on the Tensile Behaviour of Engineered Cementitious Composites - Lan, Mingzhang; Zhou, Jian; Xu, Mingfeng (Frontiers in Materials, 2021)
Engineered Cementitious Composite (ECC) is a group of ultra-ductile fibre-reinforced cementitious composites, characterized by high ductility and moderate content of short discontinuous fibre. The unique tensile strain-hardening behaviour of ECC results from a deliberate design based on the understanding of micromechanics between fibre, matrix and fibre-matrix interface. To investigate the effect of fibre properties on the tensile behaviour of ECCs is, therefore, the key to understanding the composite mechanical behaviour of ECCs. This paper presents a study on the fibre-bridging behaviour and composite mechanical properties of ECCs with three types of fibres, including oil-coated polyvinyl alcohol (PVA) fibre, untreated PVA fibre and polypropylene (PP) fibre. The experimental result reveals various fibres with different properties result in difference on the fibre-bridging behaviour and composite mechanical properties of ECCs. The difference in the composite mechanical properties of ECCs with different fibres was interpreted by analysing the fibre-bridging behaviour.